Age at first childbirth and newly diagnosed diabetes among postmenopausal women: a cross-sectional analysis of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) - Yarmolinsky, James; Duncan, Bruce Bartholow; Barreto, Sandhi Maria; Diniz, Maria de Fátima Sander; Chor, Dora; Schmidt, Maria Inês (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: It has been reported that earlier age at first childbirth may increase the risk of adult-onset diabetes among postmenopausal women, a novel finding with important public health implications. To date, however, no known studies have attempted to replicate this finding. We aimed to test the hypothesis that age at first childbirth is associated with the risk of adult-onset diabetes among postmenopausal women. DESIGN AND SETTING: Cross-sectional analysis using baseline data from 2919 middle-aged and elderly postmenopausal women in the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). METHODS: Age at first childbirth was determined from self-reporting and newly diagnosed diabetes through a 2-hour 75-g oral glucose tolerance test and/or glycated hemoglobin. Logistic regression was performed to examine associations between age at first childbirth and newly diagnosed diabetes among postmenopausal women. RESULTS: We did not find any ssociation between age at first childbirth and diabetes, either when minimally adjusted for age, race and study center (odds ratio, OR [95% confidence interval, CI]: ≤ 19 years: 1.15 [0.82-1.59], 20-24 years: 0.90 [0.66-1.23] and ≥ 30 years: 0.86 [0.63-1.17] versus 25-29 years; P = 0.36) or when fully adjusted for childhood and adult factors (OR [95% CI]: ≤ 19 years: 0.95 [0.67-1.34], 20-24 years: 0.78 [0.56-1.07] and ≥ 30 years: 0.84 [0.61-1.16] versus 25-29 years; P = 0.40). CONCLUSION: Our current analysis does not support the existence of an association between age at first childbirth and adult-onset diabetes among postmenopausal women, which had been reported previously.